School education for social and economic development in Equatorial Guinea - Nguema-Nkié, Ciriaco (2022)
Education helps man to approach his culture, to understand himself, that is to say, what he is; to be aware of what he has and what he can; it makes him capable of understanding, dominating and transforming his socio-cultural environment to live better, so that a school education adapted to the social needs of a country can contribute to the social and economic development of the country. The objective of this research was a study on the adaptation of school education in Equatorial Guinea, to contribute to the formulation of a new educational reality, adapted to the economic and social needs, which favors the social and economic development of the country, to relate the school to the local culture and to the social environment of the Equatoguineans. Methodologically, the study was framed under a qualitative, non-experimental, descriptive approach; the interview was used as a method of data collection, supported by a documentary design. Among the most relevant results, it was obtained as a general claim, the urgent need for the introduction of Equatoguinean values and socio-cultural elements in school education. And as the most significant conclusion, it can be affirmed that there is no social or economic development if school education is not adapted to the socio-cultural reality of the people, if it does not offer them the adequate tools to be able to face the different challenges of their vital environment.